Perawatan Diastema Akibat Mesiodens pada Anak Usia 9 Tahun - Suzanna Sungkar; Heriandi Sutadi (Faculty of Dentistry, Universitas Indonesia, 2015)
Mesiodens is a supernumerary tooth which is commonly found in the midline of the maxilla between the two central incisors. Supernumerary teeth are more often found in permanent than in primary teeth. Mesiodens may cause clinical disorders, such as delayed eruption or malposition of adjacent permanent teeth. Both conditions frequently result in an irregularity of developing occlusion. This paper will report mesiodens in a 9 years old girl who complained of space in the maxilla anterior teeth with anterior corssbite. The treatment included extraction of mesiodens with closing diastema and correction of the anterior crossbite with a simple orthodontic appliance. It was concluded that treatment is important to prepare space for eruption of maxillary lateral incisors, correcting diastema in the region of anterior maxilla and repairing anterior crossbite.